Airborne Microplastics: A Review on the Occurrence, Migration and Risks to Humans - Wang, Yi; Huang, Jian; Zhu, Fengxiao; Zhou, Shaoda (Bulletin of environmental contamination and toxicology, 2021)
As emerging environmental contaminants, microplastics may cause potential hazard to global ecosphere (including water, soil and air) and human health. To date, the occurance and ecological effects of microplastics in water and soil were systematically summarized. However, there are few reviews of microplastics in air (i.e. airborne microplastics). Recently, microplastics have been observed in atmospheric fallout collected from some areas. Although the studies are limited, most of the researches showed that synthetic textiles are the main source of airborne microplastics, and fibers are the dominant shape. Airborne microplastics are contributors to microplastic pollution in aquatic and soil environments. In addition, airborne microplastics can be directly inhaled and posed health risks to humans. Therefore, this review summarized the current knowledge and provide insights into further research to better understand airborne microplastics and their risks to human.